International Financial Integration and Economic Growth - Sloek, Torsten; Edison, Hali.; Levine, Ross.; Ricci, Luca. (Washington, D.C. : International Monetary Fund, 2002)
This paper uses new data and new econometric techniques to investigate the impact of international financial integration on economic growth and also to assess whether this relationship depends on the level of economic development, financial development, legal system development, government corruption, and macroeconomic policies. Using a wide array of measures of international financial integration on 57 countries and an assortment of statistical methodologies, we are unable to reject the hypothesis that international financial integration does not accelerate economic growth even when controlling for particular economic, financial, institutional, and policy characteristics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet